Assessing Customer Satisfaction in Food Cafes: A Case Study of Birgunj Metropolis - Karn , Dipesh Kumar (Intellectual Journal of Academic Research, 2025)
Birgunj is situated at southern part of Madhesh Province of Nepal. The nearby International border is Raxaul from Bihar State of India. Birgunj has cultural verities. The area is educational hub also which leads to a huge number of youths. Officers, students and youngsters tend to visit café and restaurant at celebration and leisure time. This study aims to find out the customer satisfaction level in food café regarding service quality, food taste, pricing, hygiene, and ambiance. This study aims to recommend appropriate suggestions to the restaurant and café owners to enhance customer satisfaction and business growth. The researcher has used mixed method and data have been collected by interviews, Likert 5-point scale method. Secondary information are taken from various journals, newspaper articles, books. Findings reveal high customer satisfaction with staff politeness, mobile payment options, free Wi-Fi, and digital menus. Moderate satisfaction was noted in food quality, cleanliness, ambiance, and interior design, while pricing, queue management, and smoking/family area separation scored lower. The study concludes that while digital services and staff behavior drive high satisfaction, improvements in pricing, space management, and service efficiency are essential to enhance the overall customer experience in Birgunj cafés.